Horse feathers [videorecording (Blu-Ray)] - Kalmar, Bert, 1884-1947; Ruby, Harry; Perelman, S. J. (Sidney Joseph), 1904-1979; Marx, Groucho, 1890-1977; Marx, Harpo, 1888-1964; Marx, Chico, 1887-1961; Marx, Zeppo, 1901-1979 (Universal Pictures Home Entertainment, 2023)
The four Marx Brothers Groucho, Harpo, Chico, and Zeppo are at the top of their game in the uproarious parody of college life, Horse Feathers. As president of Huxley College, the fun-loving Professor Wagstaff attempts to help his son finally graduate after 12 years by arranging to "buy" professional football players for an upcoming big game against rival Darwin University. The plan takes an unexpected twist, however, when a bootlegger and a dogcatcher are mistaken for the athletes and accidentally hired instead. Featuring their trademark insanity, including a climatic football sequence that must be seen to be believed, this quintessential Marx Brothers' comedy earned a place on the AFI's 100 Years 100 Laughs list.